CLASSIFICATION OF PNEUMONIA USING K-NEAREST NEIGHBOR METHOD WITH GLCM EXTRACTION - Wijaya, Chandra; Irsyad, Hafiz; Widhiarso, Wijang (Program Studi Teknik Informatika Universitas Multi Data Palembang, 2020)
Pneumonia is an inflammatory parenchymal disease caused by various microorganisms, including bacteria, micro bacteria, fungi, and viruses. This study used an X-ray to find out whether or not there was pneumonia. The objective of this study was to classify the X-ray results whether or not there was pneumonia in a fast and precise way through a program to produce good accuracy. The classification method used in this study were K-Nearest Neighbor (KNN) and Gray Level Co-Occurrence (GLCM) for the extraction method. There are several stages before being classified, namely cropping, resizing, contrast stretching, and thresholding. The results showed that the best accuracy per class was 66.20% for K = 5.